Pemanfaatan Pembelajaran Bahasa Indonesia dalam Kesulitan Menulis Surat Menyurat di SMP Darussalam Jakarta - Rahmawati Rahmawati; Anggun Citra Dini Puspita Sari (Departement of Mathematics Education, 2023)
This study aims to determine the use of learning Indonesian in the difficulty of writing correspondence at SMP Darussalam. In order to achieve this goal, library and observation methods are used. The data obtained was first classified before being analyzed. The method used is descriptive method and contextual method, while writing difficulties will discuss the technique of writing correspondence. The type of research used in this research is descriptive quantitative research. Quantitative descriptive is a research design that describes research variables in the form of statistical figures which can later provide an overview of the difficulty of writing letters for class IX students of SMP Darussalam. The population in this study were all students of class IX at SMP Darussalam which consisted of 35 students. The sample in this study was carried out by means of positive sampling. Sampling technique with certain considerations. The results of the research were the difficulties of class IX students of SMP Darussalam in writing official letters which were categorized as quite difficult because the results obtained had an average score of 69.5 which is in the 56-74 value interval. The lowest score of 13.8 is in the 10-55 value interval, which is very difficult, while the highest score is 93.3 and is in the 86-100 value interval, which is very difficult.